Measurement and prediction of sound absorption of room surfaces and contents at low frequencies - Melo, Gustavo da Silva Vieira de (2002)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico. Programa de Pós-Graduação em Engenharia Mecânica.